2016
DOI: 10.1136/vetreccr-2015-000285
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal metastatic cutaneous and mucosal transmissible venereal tumour in a female puppy

Abstract: An eight-month old female entire mixed breed dog in Arizona was presented for a 15-day history of multifocal cutaneous nodules and plaques, with progressive stertor, anorexia, haemorrhagic gingival masses, peripheral lymphadenopathy and mild haemorrhagic vaginal discharge without obvious genital masses. Fine needle aspirate cytology was consistent with multifocal cutaneous and mucosal canine transmissible venereal tumour (TVT) with peripheral lymph node metastases. Histopathology and immunohistochemistry suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Especially in young dogs tumor is excessively tended to metastasis [6,9,11]. Furthermore, Laporte et al [7] reported a TVT case metastasized to cutaneous, rostral face, gingiva in the 8-month old bitch.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in young dogs tumor is excessively tended to metastasis [6,9,11]. Furthermore, Laporte et al [7] reported a TVT case metastasized to cutaneous, rostral face, gingiva in the 8-month old bitch.…”
Section: Discussionmentioning
confidence: 99%